Respiratory symptoms and airway obstruction in HIV-infected subjects in the HAART era. - M Patricia George; Mouhamed Kannass; Laurence Huang; Frank C Sciurba; Alison Morris (PLoS ONE)
Background Prevalence and risk factors for respiratory symptoms and airway obstruction in HIV-infected subjects in the era of highly active antiretroviral therapy (HAART) are unknown. We evaluated respiratory symptoms and measured airway obstruction to identify the impact of HAART and other risk factors on respiratory symptoms and pulmonary function. Methodology/principal findings Two hundred thirty-four HIV-infected adults without acute respiratory symptoms were recruited from an HIV clinic. All subjects were interviewed and performed spirometry. Multivariate linear and logistic regressions were performed to determine predictors of respiratory symptoms, forced expiratory volume in one second (FEV(1)) percent predicted, and FEV(1)/forced vital capacity (FEV(1)/FVC). Thirty-one percent of subjects reported at least one respiratory symptom. Smoking status (current or former versus never) (odds ratio [OR] = 2.7, 95% confidence interval [CI] = 1.41-5.22, p = 0.003), higher log plasma HIV viral levels (OR = 1.12, 95%CI = 1.02-1.24, p = 0.02), and lower FEV(1)/FVC (OR = 1.06 for every 0.01 decrease in FEV(1)/FVC, 95%CI = 1.02-1.14, p = 0.001) were independent predictors of respiratory symptoms. Age (p = 0.04), pack-year smoking history (p<0.001), previous bacterial pneumonia (p = 0.007), and HAART use (p = 0.04) were independent predictors of decreased FEV(1)/FVC. Conclusions/significance Respiratory symptoms remain common in HIV-infected subjects, especially in those with a smoking history. Subjects who were older, had a greater pack-year history of smoking, or previous bacterial pneumonia had lower FEV(1)/FVC ratios. Interestingly, use of HAART was independently associated with a decreased FEV(1)/FVC, possibly secondary to an immune response to subclinical infections, increased autoimmunity, or other factors associated with HAART use.